Primary vs. Secondary Heart Failure Diagnosis: Differences in Clinical Outcomes, Healthcare Resource Utilization and Cost - Bueno, Héctor; Goñi, Clara; Salguero-Bodes, Rafael; Palacios, Beatriz; Vicent, Lourdes; Moreno, Guillermo; Rosillo, Nicolás; Varela, Luis; Capel, Margarita; Delgado, Juan; Arribas, Fernando; del Oro, Manuel; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. There is scarce information on patients with secondary heart failure diagnosis (sHF). We aimed to compare the characteristics, burden and outcomes of sHF with those with primary HF diagnosis (pHF). Methods. Retrospective, observational study on patients ≥18 years with emergency department (ED) visits during year 2018 with pHF and sHF in ED or hospital (ICD-10-CM) diagnostic codes. Baseline characteristics, 30-day and 1-year mortality, readmission and re-ED visit rates and costs were compared between sHF and pHF. Results. Of 797 patients discharged home from the ED, 45.5% had sHF, and these presented lower 1-year hospitalization and re-ED visit rates, and costs. In contrast, of 2286 hospitalized patients, 55% had sHF and 45% pHF. Hospitalized sHF patients had significantly (p<0.01) greater comorbidity, lower use of recommended HF therapies, longer length of stay (10.8±10.1 vs 9.7±7.9 days, p=0.001), and higher in-hospital and 1-year mortality (32% vs 25.8%, p=0.001) with no significant differences in readmission rates, and lower 1-year re-ED visit rate. Hospitalized sHF patients had higher total costs (€12,262,422 vs €9,144,952, p<0.001), mean cost per patient-year (€9,755±13,395 vs €8,887±12,059, p<0.001), and average daily cost per patient. Conclusions. Hospitalized sHF patients have worse initial prognosis, greater use of healthcare resources and higher costs.